Perjanjian Jasa Titip Beli Barang melalui Platform E-Commerce: Studi Kasus Perlindungan Konsumen - Agussalim A. Gadjong (CV. Social Politic Genius (SIGn), 2022)
This research examines and analyzes the legal relationship and protection between service providers and consumers in the agreement of personal shopping services through e-commerce platforms. This empirical legal research was conducted in Makassar from December 2022 to February 2023. Data is collected through direct interviews with the two informants and questionnaires for the 30 respondents. The obtained data is then quantitatively analyzed and presented in argumentative and infographic forms to describe the problem and address the research purposes. The results show that the legal relationship occurring in personal shopping service transactions can be categorized as a legal relationship of sale and purchase because there is no substantial difference in the elements. In principle, the service provider can be held accountable if the consumer suffers a loss due to the non-fulfillment of legal obligations within the transaction. In this research, the service provider has fulfilled its obligation to provide compensation, damages, or product replacements if the products consumers receive do not conform to the agreement of personal shopping service through e-commerce platforms. Therefore, it is recommended that consumers should be diligent in understanding the agreement’s terms and conditions of personal shopping services. Service providers must ensure transparent communication, maintain high-quality services, and fulfill their obligations by providing compensation or product replacements when necessary. Meanwhile, the Government should establish and enforce regulations to protect service providers and consumers, creating a fair and reliable e-commerce environment for personal shopping services. In addition, these regulations are also intended to prevent fraud that can be detrimental to all parties in the agreement of personal shopping services through e-commerce platforms in the future.